創意自我效能、工作價值觀對教師創造力教學影響之研究：專業學習社群與 教師信任的跨層次分析 Effects of Creative Self-Efficacy and Work Value on Creative Teaching: A Cross-Level Analysis of Professional Learning Communities and Teachers' Trust - 蕭佳純 Chia-Chun Hsiao (National Taiwan Normal University, 2022)
有鑑於專業學習社群近年受到愈來愈多研究的重視，但缺乏對於創造力教學行為之探討，故本研究以創意自我效能、工作價值觀、專業學習社群對教師創造力教學影響為探討主軸，兼論教師信任對專業學習社群的影響、教師信任的多層次調節效果及專業學習社群的多層次中介效果。研究對象為30個社群，214位國小教師，藉由階層線性模式分析結果顯示，當專業學習社群中的支持合作、共享教學愈好、正向肯定、成就聲望愈積極，則提升創造力意向會愈好；而願景領導、共享教學愈好、正向肯定、成就聲望愈積極，則增進創造力技能也會愈好。較為重要的研究發現是，主管信任、同事信任分別和創新發展與人際關係產生交互作用，對提升創造力意向產生正向調節；主管信任、組織信任分別和組織安全與創新發展產生交互作用，對增進創造力技能產生正向調節。再者，專業學習社群中的願景領導是一個相當重要的變項，因為它不僅會對提升創造力意向及增進創造力技能有直接影響，更重要的是，主管信任還可以透過它的中介對創造力教學產生間接影響。所以專業學習社群運作的願景與目標必須要關注在學生學習，並成為行政人員與教師努力的依據，於此，本研究再次強調願景領導的實務價值與重要性。 Main Purpose and Motivation Numerous developed countries have demonstrated that professional learning communities can improve teaching quality for young generations through dialogue, support, class observation, sharing, and cooperation. Professional learning communities have received increasing research attention, but few studies have investigated creative teaching or performed cross-level analyses of factors that affect it. Thus, this study investigated the effects of creative self-efficacy, work values, and professional learning communities on creative teaching. Key variables were identified through a literature review. The objectives were to determine whether (1) professional learning communities directly affect creative teaching, (2) teacher trust indirectly affects creative teaching through professional learning communities as a mediating variable, (3) work values directly affect creative teaching, (4) teachers' creative self-efficacy directly affects creative teaching, (5) teacher trust indirectly affects the relationship between their work values and creative teaching, and (6) teacher trust indirectly affects the relationship between their creative self-efficacy and creative teaching. Research Method This study performed a multilevel analysis of professional learning communities. Community leaders and directors were asked to obtain informed consent from the community members and to distribute questionnaires to teachers in public and private schools. A total of 30 communities and 214 elementary school teachers were sampled; 57 of the teachers were men, and 152 were women. Hierarchical linear modeling was performed to test six hypotheses and determine the effects and relationships among the variables. Research Results The leaders encouraged cooperation and exchange among the professional learning communities, which increased creative intention and improved performance. Visionary leadership, sharing-based teaching, positive affirmations, and the achievement of goals positively affected creative skills. In addition, trust among supervisors and colleagues positively affected innovation, interpersonal relationships, and creativity. Thus, innovation develops from a sense of security and trust. Trust in supervisors and the organization affected organizational security and innovation, respectively, and strengthened creative skills, thereby increasing the teachers' willingness to share experiences with each other and devote their creativity to their organization. Suggestions Visionary leadership is essential in professional learning communities because it not only directly affects creative intention and skills but also indirectly affects trust in supervisors through creative teaching as a mediating variable. Creative intention develops when subordinates feel trust and the security to experiment. Thus, the visions and goals of professional learning communities must be closely related to teachers' learning needs and provide a foundation for administrators, highlighting the practical value of visionary leadership. Research Discussion and Suggestion Most studies on creative teaching have performed teacher-level analyses and neglected factors related to schools. This study examined teachers' personal factors (creative self-efficacy and work values) and investigated creative teaching. The teachers' work environments (professional learning communities and teacher trust) were also considered. In addition, this study explored several related variables to fill gaps in the literature. This study also offered several specific and practical suggestions to improve professional learning communities, teacher trust, creative self-efficacy, and work values. First, professional learning community leaders can improve creative teaching through visionary leadership and by considering teachers' opinions and addressing their needs, thereby gaining support from the community. Second, principals and supervisors should analyze teachers' professional learning communities, provide communication channels, fulfil hardware and software requirements, and address teachers' needs to build trust. Third, teachers must gain the trust of their colleagues to establish healthy interpersonal professional relationships. Mutual trust and support can also lead to creative teaching. Subsequent studies should investigate these topics in other contexts, such as middle schools, high schools, and colleges, to identity differences among educational levels and background variables.